2017
DOI: 10.1017/s003329171700277x
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal mediation analysis of the effect of negative-self-schemas on positive symptoms via negative affect

Abstract: Our findings support the postulated affective pathway from NSS to positive symptoms via negative affect. Specifically, our data indicate that NSS and negative affect influence each other and build up over the course of several months before leading on to positive symptoms. We conclude that interrupting this process by targeting NSS and negative affect early in the process could be a promising strategy to prevent the exacerbation of positive symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
25
1
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(34 citation statements)
references
References 58 publications
(81 reference statements)
4
25
1
3
Order By: Relevance
“…However, to date, the mechanisms whereby these experiences then convert to interpersonal sensitivity are not well understood. Although there are emerging longitudinal studies to suggest a unidirectional pathway from negative self-schemas more broadly to paranoia (Fowler et al 2012; Oliver et al 2012; Jaya et al 2017), the role of interpersonal sensitivity in these pathways has not been investigated. A recent study has shown that interpersonal sensitivity mediated the association between childhood bullying victimisation and paranoia (McDonnell et al 2018), but because the design was cross-sectional, causality could not be established.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, the mechanisms whereby these experiences then convert to interpersonal sensitivity are not well understood. Although there are emerging longitudinal studies to suggest a unidirectional pathway from negative self-schemas more broadly to paranoia (Fowler et al 2012; Oliver et al 2012; Jaya et al 2017), the role of interpersonal sensitivity in these pathways has not been investigated. A recent study has shown that interpersonal sensitivity mediated the association between childhood bullying victimisation and paranoia (McDonnell et al 2018), but because the design was cross-sectional, causality could not be established.…”
Section: Discussionmentioning
confidence: 99%
“…More recent social‐cognitive models suggest that loneliness plays a causal role in paranoia because feeling lonely is characterized by several negative schemas about the self and others, resulting in a heightened sensitivity to threat and decreased trust in interpersonal relationships (Jaya, Ascone, & Lincoln, 2018; Lamster, Lincoln, Lincoln, Nittel, Rief, & Mehl, 2017; Lamster, Nittel, Nittel, Rief, Mehl, & Lincoln, 2017). Much less is known about the relationship between loneliness and other psychotic symptoms.…”
Section: Evidence‐based Practice (Knowledge)mentioning
confidence: 99%
“…Psychological models of psychosis have long recognized the role of emotion in the development, maintenance, and treatment of psychosis (Freeman, Garety, Kuipers, Fowler, & Bebbington, ; Garety, Kuipers, Fowler, Freeman, & Bebbington, ; Morrison, ). High levels of negative emotion (primarily anxiety and depression) are common in individuals with psychosis and are associated with, and can be predictive of, psychotic symptoms and recovery from psychosis (Freeman & Garety, ; Freeman et al, ; Hartley, Barrowclough, & Haddock, ; Jaya, Ascone, & Lincoln, ; So et al, ). There is also emerging evidence that psychological interventions specifically targeting negative emotions are efficacious (Opoka, Ludwig, & Lincoln, ).…”
Section: Introductionmentioning
confidence: 99%